2013
DOI: 10.7567/jjap.52.05eb04
|View full text |Cite
|
Sign up to set email alerts
|

Negative Impact of Etched Si Area on Selectivity and Positive Impact of Photoelectric Current on Etched Profile in Gate Etching with Different Wafer Bias Frequencies

Abstract: The effect of wafer-bias frequency on the dummy-gate fabrication of fin-shaped field-effect transistor (Fin-FET) was investigated. The clear difference in the selectivity of polycrystalline silicon to SiO2 between 400 kHz and 13.56 MHz decreased when the etched Si area increased. On the other hand, a higher frequency increased such selectivity when Si area decreased. These results can be explained by the effect of by-product deposition. As for the etched profile, the amount of side etching was much larger at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…82,83) Kamibayashi et al discussed the effect of wafer bias frequencies on etched profiles. 99) Negishi and co-workers reported that the mask edge roughness was transferred with amplification of the roughness amplitude, leading to deformed pattern profiles with profile distortion at the hole bottom. 100,101) Such profile distortion problems have always been an issue for the plasma-etching fabrication of HAR features.…”
Section: Har Feature Profile Control: From Two Dimensions To Three Di...mentioning
confidence: 99%
“…82,83) Kamibayashi et al discussed the effect of wafer bias frequencies on etched profiles. 99) Negishi and co-workers reported that the mask edge roughness was transferred with amplification of the roughness amplitude, leading to deformed pattern profiles with profile distortion at the hole bottom. 100,101) Such profile distortion problems have always been an issue for the plasma-etching fabrication of HAR features.…”
Section: Har Feature Profile Control: From Two Dimensions To Three Di...mentioning
confidence: 99%